2016
DOI: 10.1007/s10495-016-1270-1
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids of Rosa roxburghii Tratt exhibit radioprotection and anti-apoptosis properties via the Bcl-2(Ca2+)/Caspase-3/PARP-1 pathway

Abstract: The objective of our study was to assess the radioprotective effect of flavonoids extracted from Rosa roxburghii Tratt (FRT) and investigate the role of Bcl-2(Ca(2+))/Caspase-3/PARP-1 pathway in radiation-induced apoptosis. Cells and mice were exposed to (60)Co γ-rays at a dose of 6 Gy. The radiation treatment induced significant effects on tissue pathological changes, apoptosis, Ca(2+), ROS, DNA damage, and expression levels of Bcl-2, Caspase-3 (C-Caspase-3), and PARP-1. The results showed that FRT acted as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 40 publications
5
45
0
Order By: Relevance
“…Caspase-3 activation subsequently leads to DNA breakage, nuclear chromatin condensation, and apoptosis. 6,[42][43][44] As our data show, CS has induced intrinsic mitochondria-mediated apoptosis in a caspase-3-dependent manner, accompanying collapse of mitochondrial membrane potential and ROS production from mitochondria into the cytoplasm. This indicates that mitochondrial dysfunction may have occurred during CS-induced MDA-MB-231 cells death.…”
Section: Discussionsupporting
confidence: 58%
“…Caspase-3 activation subsequently leads to DNA breakage, nuclear chromatin condensation, and apoptosis. 6,[42][43][44] As our data show, CS has induced intrinsic mitochondria-mediated apoptosis in a caspase-3-dependent manner, accompanying collapse of mitochondrial membrane potential and ROS production from mitochondria into the cytoplasm. This indicates that mitochondrial dysfunction may have occurred during CS-induced MDA-MB-231 cells death.…”
Section: Discussionsupporting
confidence: 58%
“…Caspase-3 is a physiological enzymatic protease of Bcl-2 involved in the process of apoptosis (41). In the current study, overexpression of miR-140-5p in A549 cells markedly inhibited YES1 and Bcl-2 expression; however, the protein expression levels of Bax and caspase-3 were upregulated following transfection with miR-140-5p, compared with the NC group.…”
Section: Discussionmentioning
confidence: 43%
“…A variety of apoptosis-stimulating factors initiate different protease cutting of prokaryogen caspase3 and activate caspase3, and the activated caspase3 further cuts different substrates, leading to the amplification of protease cascade reaction cutting and finally leading to apoptosis of cells. Caspase3 is a necessary pathway for the cascade of apoptotic proteins [21]. In this study, our results demonstrated that the cleaved caspase3 and PARP were activated through up-regulating of Cav1.3 after PGE2 stimulation.…”
Section: Discussionsupporting
confidence: 56%